La música ecuatoriana en la interculturalidad - Atiaja Alvarez, Jaime Leonidas (2017)
The music in Ecuador is a source of cultural wealth, however actually its real importance has now left side and like this transcends in education, and encourages the intercultural. This research was of great importance because it strengthens Ecuadorian traditional music and ancient music, which is a living sign of the Ecuadorian culture. Children need chances to play, sing, listen to music of different genres in this way they will enrich your language; they develop the ability to perceive the rhythm and harmony, as well as memory, attention, listening, for that reason was taken as a sample of the research the province of Cotopaxi Salcedo Cantón Mulliquindil Santa Ana parish, children in General educational unit "Emilio Terán" spreading and consolidating the culture. It is essential to promote our roots because they will always be afloat to remember that Ecuadorian music is part of our identity therefore it will be the main function of the project to keep latent our traditions....